IMPACT OF MICRO CREDIT SCHEME FOR PERSONS WITH PHYSICAL DISABILITIES IN HERAT, AFGHANISTAN. - Jean Fiasse (Disability, CBR and Inclusive Development, 2011)
The present study presents the results and impact of the micro credit scheme of the International Committee of the Red Cross (ICRC) physical rehabilitation centre in Herat, Afghanistan. The author used a descriptive method to retrospectively analyse the data. Results showed that the repayment rate is 70% and impact 6 months after completing the loan is that 65% of the clients continued with their business, showing improved confidence and living conditions.  There was an element of “exclusion by others”, which should be studied further and analysed through interactions with the neighbourhood community during the first interview at the client’s home. When necessary, an awareness programme should be carried out within the community.  “Exclusion by staff” appears to exist for persons with paraplegia, as there is a trend to prioritise the sustainability of the scheme instead of its accessibility to the most vulnerable groups. Since the beginning of 2009 however, efforts are under way to register persons with paraplegia and to involve physiotherapists in their follow- up. Key words: Impact of micro-credit, persons with disabilities, Afghanistan DOI 10.5463/DCID.v22i1.8